Österreichisches Deutsch macht Schule Bildung und Deutschunterricht im Spannungsfeld von sprachlicher Variation und Norm - de Cillia, Rudolf (2019)
The book at hand deals with the topics of language-internal multilingualism and linguistic variation, pluricentricity and Austrian German in the realm of school and education in Austria. A large empirical survey among teachers and students focused on the conceptualization of German in Austria, the attitudes towards the standard varieties of German, norm concepts and teachers` correction practice, and language use in German lessons.